The Analysis of Filtration Efficiency to Reduce BOD and COD Levels in Domestic Waste at the Communal WWTP of Bilebante Village, Pringgarata District, Central Lombok - Nurhidayah, Nurhidayah; Sholehah, Hijriati; Al-Qarni, Jisul (Jurnal Pijar Mipa, 2024)
This research aims to determine the level of reduction in BOD and COD in household wastewater after the filtration process and to determine the efficiency of the filter media in reducing BOD and COD in sewage. The research was conducted in Bilebante village, Central Lombok Regency, NTB. The method takes three wastewater samples at different locations before and after the filtration stage. The results of the research show that the COD concentration in domestic wastewater before going through the processing process using filtration media obtained a result of 63 mgl/L, then at the filtration stage using plastic bottle media, the result was 34 mgl/L with an efficiency value of 46%, and at the filtration stage using activated carbon media, a value of 12 mgl/L was obtained so that the resulting efficiency value was 64%. The results of the BOD concentration in domestic wastewater before going through the processing process using filtration media obtained an initial result of 1.6 mgl/L; then, at the filtration stage using plastic bottle media, the result was 0.6 mgl/L with an efficiency value of 62 %. At the filtration stage using active carbon media, a value of 0 mgl/L was obtained, with an efficiency value of 100%. This research concludes that wastewater is safe to use, whether for watering plants or other things because there is a decrease in levels of COD and BOD that meet quality standards.